Different selectivities in the insertions into C(sp2)-H bonds: Benzofulvenes by dual Gold catalysis competition experiments - Plajer, Alex; Ahrens, Lukas; Wieteck, Marcel; Lustosa, Danilo Machado; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Chemistry - a European journal, 2018)
An unprecedented, often almost quantitative access to tricyclic aromatic compounds by dual gold catalysis was developed. This synthetic route expands the scope of benzofulvene derivatives through a C(sp2)-H bond insertion in easily available starting materials. The insertion takes place with an exclusive chemoselectivity with respect to the competing aromatic C-H positions. A bidirectional synthesis with two competing ortho-aryl C-H bonds in the selectivity-determining step also shows perfect selectivity; this result is explained by a computational investigation of the two conceivable intermediates. The intramolecular competition of two non-equivalent aryl C-H bonds with a benzylic methyl group also showed perfect selectivity.